Low-Grade Adenosquamous Carcinoma of the Breast: Imaging and Histopathologic Characteristics of this Rare Disease. Issue 4 (November 2013) - Scali, Elena P.; Ali, Rola H.; Hayes, Malcolm; Tyldesley, Scott; Hassell, Patricia
Low-grade adenosquamous carcinoma is a rare histologic subtype of breast carcinoma that has a variable mammographic and sonographic appearance, which overlaps with both benign and malignant neoplasms. Because of its lack of unique imaging features, a diagnosis of low-grade adenosquamous carcinoma is based on histopathology. The recognition of this entity is an important consideration in the differential diagnosis of breast masses and carries implications for prognosis, which is more favorable than other types of breast carcinoma.